2020
DOI: 10.1016/j.agsy.2019.102768
|View full text |Cite
|
Sign up to set email alerts
|

Forest fragments and natural vegetation patches within crop fields contribute to higher oilseed rape yields in Brazil

Abstract: Ecosystem services are fundamental to the maintenance of biodiversity, food security, livestock and biofuel production. Here, we analyze the impact of the distance between forest fragments and oilseed crops (Brassica napus) on the crops' yield (kg/ha) and economic value (US$). For crop yield, the total loss field −1 was calculated as the difference between the most lucrative parcel and the least lucrative parcel. Hypothetical models were developed to estimate the potential changes in crop incomes due to progre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 55 publications
1
11
0
1
Order By: Relevance
“…Often fragmented or diverse agricultural landscapes are associated with positive effects on pollinator populations (Krishnan et al 2012;Chakraborty et al 2021). In such landscapes pollinators benefit from forest patches, field margins, and other natural habitats between agricultural plots (Priess et al 2007;Tibesigwa et al 2019;Halinski et al 2020;Viswanathan et al 2020). We also find evidence of such a positive association.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…Often fragmented or diverse agricultural landscapes are associated with positive effects on pollinator populations (Krishnan et al 2012;Chakraborty et al 2021). In such landscapes pollinators benefit from forest patches, field margins, and other natural habitats between agricultural plots (Priess et al 2007;Tibesigwa et al 2019;Halinski et al 2020;Viswanathan et al 2020). We also find evidence of such a positive association.…”
Section: Discussionsupporting
confidence: 59%
“…1 Here, scale dependencies play a critical role. Several ecological studies demonstrate the importance of landscape scale, structure, composition, and configuration in defining pollination services to account for pollinator mobility and foraging ranges (Tscharntke et al 2005;Kremen et al 2007;Halinski et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Dense Caatinga patches have a higher conservation priority than open Caatinga patches within our study area, characterized by rapid expansion and intensification of agriculture, as they provide higher ecosystem services and protection against anthropogenic disturbance and aridity for functional diversity [75]. In fact, a recent study from Brazil found the loss of forests across agricultural landscapes to have a negative effect on agricultural productivity by reducing crop pollination [76]. As a result, within our study region, conservation priority was given to dense Caatinga patches, while open Caatinga patches were prioritized for restoration, as they have a reduced capacity for natural regeneration and contain grasses and abandoned areas [44].…”
Section: Prioritization Of Caatinga Patches To Conserve and Restorementioning
confidence: 85%
“…According to our results, environment enrichment by increasing aspects of floral diversity resulted in higher visitation rates. In nature, environments presenting diversified floral characteristics have been shown to benefit the reproductive output of plants and can result in greater yields [ 64 ]. Ultimately, it can also ameliorate the reproductive output of pollinators by increasing offspring survival and nest development.…”
Section: Discussionmentioning
confidence: 99%
“…In a network context, a positive association between increased linkage density and pollination was also found [ 7 , 72 ]. Thus, if our findings are applied to pollination systems in more diverse agricultural environments, adding flower types (e.g., wildflowers strips) rather than maintaining monocrops, would likely provide a higher yield if flower visitation rate is performed by an efficient pollinator [ 64 , 73 ].…”
Section: Discussionmentioning
confidence: 99%